Pemanfaatan Media Pembelajaran Macromedia Flash Mata Pelajaran Sejarah Kelas X MAN 2 Bandar Lampung - Arif Rahman Muhayat; Maskun Maskun; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2018)
The aim of this research is to know the increasing of student cognitive domain studying on learning with macromedia flash learning on history subject of X grade social science in MAN 2 Bandar Lampung on academic year 2016/2017. Problem formulation of this research is “what accour in increasing studying result on cognitive domain on learning by utilizing macromedia flash learning on history subject of X grade social in MAN 2 Bandar Lampung?” The research method used is an experimental method with a qualitative approach, one-shot case study design. According to the research, it is concluded that learning by utilizing macromedia flash interactive multimedia learning cs 8 can increase the studying result of student cognitive domain.Tujuan dari penelitian ini adalah untuk mengetahui peningkatan hasil belajar ranah kognitif siswa pada pembelajaran dengan media pembelajaran macromedia flash Mata Pelajaran Sejarah Kelas X MAN 2 Bandar Lampung 2016/2017. Rumusan masalah dalam penelitian ini adalah “Apakah terjadi peningkatan hasil belajar ranah kognitif pada pembelajaran dengan memanfaatkan media Pembelajaran Macromedia Flash Mata Pelajaran Sejarah Kelas X MAN 2 Bandar Lampung?.” Metode penelitian yang digunakan adalah metode eksperimen dengan pendekatan kualitatif, desain one-shot case study. Berdasarkan hasil penelitian disimpulkan bahwa pembelajaran dengan memanfaatkan media pembelajaran macromedia flash dapat meningkatan hasil belajar ranah kognitif siswa.Kata kunci: macromedia flash, pemanfaatan, sejarah